Health-related quality of life results from the phase III CheckMate 067 study. (September 2017) - Schadendorf, Dirk; Larkin, James; Wolchok, Jedd; Hodi, F. Stephen; Chiarion-Sileni, Vanna; Gonzalez, Rene; Rutkowski, Piotr; Grob, Jean-Jacques; Cowey, C. Lance; Lao, Christopher; Wagstaff, John; Callahan, Margaret K.; et al.
Abstract: Background: Nivolumab, a monoclonal antibody of immune checkpoint programmed death 1 on T cells (PD-1), combined with ipilimumab, an immune checkpoint cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) inhibitor, as combination therapy on the one hand and nivolumab as monotherapy on the other, have both demonstrated improved efficacy compared with ipilimumab alone in the CheckMate 067 study. However, the combination resulted in a higher frequency of grade 3/4 adverse events (AEs), which could result in diminished health-related quality of life (HRQoL). Here we report analyses of HRQoL for patients with advanced melanoma in clinical trial CheckMate 067. Patients and methods: HRQoL was assessed at weeks 1 and 5 per 6-week cycle for the first 6 months, once every 6 weeks thereafter, and at two follow-up visits using the European Organization for Research and Treatment of Care Core Quality of Life Questionnaire and the EuroQoL Five Dimensions Questionnaire. In addition to the randomised population, patient subgroups, including BRAF mutation status, partial or complete response, treatment-related AEs of grade 3/4, and those who discontinued due to any reason and due to an AE, were investigated. Results: Nivolumab and ipilimumab combination and nivolumab alone both maintained HRQoL, and no clinically meaningful deterioration was observed over time compared with ipilimumab. In addition, similar results were observed across patient subgroups, and no clinically meaningful changes in HRQoL were observed during follow-up visits for patients who discontinued due to any cause. Conclusion: These results further support the clinical benefit of nivolumab monotherapy and nivolumab and ipilimumab combination therapy in patients with advanced melanoma. The finding that the difference in grade 3/4 AEs between the arms did not translate into clinically meaningful differences in the reported HRQoL may be relevant in the clinical setting. Study number: NCT01844505. Highlights: Nivolumab + ipilimumab combination and nivolumab alone show increased efficacy versus ipilimumab. Nivolumab + ipilimumab combination resulted in a higher frequency of grade 3/4 adverse events (AEs). Increased AE frequency could result in diminished health-related quality of life (HRQoL). Nivolumab + ipilimumab combination and nivolumab alone maintained HRQoL. Varied subgroup population results supported randomised population results.